Influence of Spin Fluctuation on the Magnetic Properties of EuO Ultra-thin Film - Thao, Pham Huong; Cong, Bach Thanh (Communications in Physics, 2013)
The Gaussian spin fluctuation theory is applied to study magnetic properties (Curie temperature, magnetization) of EuO  ultra-thin films within nearest neighbor and next nearest neighbor exchange approximation. The dependence of Curie temperature on the thickness of the free EuO ultrathin film is calculated and compared with the results of the other mean field method- constant coupling approximation. The effect of nearly independence of saturation magnetization on the EuO films thickness measured  in [8] can be explained by controlling the next nearest neighbor exchange in presence of substrates